Application of vocal techniques for soprano and alto in choir performance / Noor Shahida Jamaluddin - Jamaluddin, Noor Shahida (2014)
The purpose of this study is to discuss the application of vocal techniques for soprano and alto in choir performance. To be more in depth, this study aims to get the answer of the problems faced by student in singing soprano and alto, the effective techniques for soprano and alto and the effect of using correct vocal techniques in choir performance. The research is conducted by questionnaire randomly to the 50 music students who were taking choir class. The finding from this research was analysed and all of the respondents answer the questionnaire to get the effective techniques that can improve their singing especially for soprano and alto in choir performance